Cervical rib - a clinical case report - V Lokanayaki (Wolters Kluwer Medknow Publications, 2014)
The cervical rib is surgically important than being just anatomical curiosity alone. The distal parts of costal processes in seventh cervical vertebra occasionally develop as cervical rib. A 32 years old female patient who attended the vascular surgical department presented with features of cervical rib on the left side. Imaging procedures confirmed bilateral cervical rib for which the patient underwent surgery. The cervical rib can cause thoracic outlet syndrome with features of acute arterial occlusion in upper limb. This case is reported to stress the important complications due to the cervical rib.